Reliability, validity, and factorial structure of the Turkish version of the Structured Inventory of Malingered Symptomatology (Turkish SIMS) - Kose, Samet; Ardic, Ferhat Can; Solmaz, Mustafa; Kulacaoglu, Filiz; Balcioglu, Yasin Hasan (TAYLOR & FRANCIS LTD, 2019)
Objective: Smith and Burger developed the Structured Inventory of Malingered Symptomatology (SIMS) in 1997 as a self-report measure for malingering of psychiatric symptoms. The SIMS consists of 75 dichotomous (True-False) items that form into five subscales Psychosis (P), Neurologic Impairment (NI), Affective Disorder (AF), Amnestic Disorders (AM), Low Intelligence (LI); each subscale containing 15 items. In this study, we aimed to examine the reliability, validity, and factor structure of the SIMS in a Turkish forensic psychiatry sample. Methods: A sample of 103 forensic patients (9 female, 94 male), aged 18-75, undergoing an inpatient forensic evaluations for competency to stand trial (CST) were recruited from a large forensic hospital in Turkey. The study protocol was approved by the local Ethics Committee. Sociodemographic information of the participants was collected and the SIMS, Miller Forensic Assessment of Symptoms Test (M-FAST), the Scales of Psychological Well-being, 36-Item Short Form Survey (SF-36), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were administered. All statistical analyses were performed by using SPSS version 23.0 for Windows. Results: The Cronbach's alpha coefficients for the Turkish SIMS were ranging from 0.32 to 0.88. The lowest alpha coefficient was observed for the Low Intelligence (0.32). For the whole scale, Cronbach's alpha coefficient was found to be 0.93. The test-retest (at after 1 week) correlation coefficients for Psychosis (P), Neurologic Impairment (NI), Affective Disorder (AF), Amnestic Disorders (AM), Low Intelligence (LI), and whole scale were found to be 0.97, 0.98, 0.96, 0.67, 0.83, and 0.95, respectively. A positive and statistically significant correlation was found between the Turkish SIMS and BDI (r = 0.620, p < .01), BAI (r = 0.597, p < .01), M-FAST subscale Reported versus Observed Symptoms (r = 0.675, p < .01), M-FAST subscale Extreme Symptomatology (r = 0.713, p < .01), M-FAST subscale Rare Combinations (r = 0.751, p < .01), M-FAST subscale Unusual Hallucinations (r = 0.710, p < .01), M-FAST subscale Unusual Symptom Course (r = 0.588, p < .01), M-FAST subscale Negative Image (r = 0.528, p < .01), M-FAST subscale Suggestibility (r = 0.440, p < .01), and MFAST Total (r = 0.816, p < .01) scores. Principal axis factor analyses with Promax rotation were performed and four-factor solution that accounted for 39.87% of the variance observed. Conclusions: Our preliminary findings suggested that Turkish SIMS was a valid and reliable tool with a robust factorial structure for further use in detecting malingering of forensic psychiatric cases in Turkey.
Keywords: Structured Inventory of Malingered Symptomatology; reliability; validity; factor structure